Pemidanaan Terhadap Mucikari Ditinjau dari Asas Keadilan dalam Kasus Trafficking Anak - Setiyo Wicaksono, Bambang; Pratama Hapsari, Ifahda (LPPM Universitas Ekasakti Padang, 2024)
There are many cases of illegal exploitation that occur now based on paper and electronic media reports and many examination results show that cases of illegal exploitation, especially of women and children, need attention. Dealing with women and children in Indonesia generally involves prostitution and pornography. The occurrence of sexual trafficking involving girls reveals violations of women's human rights, depriving them of the opportunity to experience peace and happiness from a young age. Their basic rights to live freely and protect themselves from potential harm have been reduced due to criminal activities. These incidents show a correlation between the trafficking of underage girls (through prostitution) and other sexual offenses such as assault and battery. Many minors and adult women are victims. Brutality against women is thought to stem from a framework that considers women as weak and substandard individuals compared to men. Overall, victims of human trafficking, especially women involved in prostitution and children forced to work, are victims of crime and not perpetrators of crime.